Consumidoras especializadas : trajetórias de consumo e venda de cosméticos - Passos, Luana Paula Peixoto Aglio dos (2012)
The research, begun in 2009, is characterized as qualitative, with ethnographic bias. From participant observation (made at regular meetings of cosmetics dealers of Naura’s brand or the sale of such products), and data from interviews conducted with four